The Antibacterial Efficacy of Photo-Activated Disinfection, Chlorhexidine and Sodium Hypochlorite in Infected Root Canals: An in Vitro Study - Samiei, Mohammad; Shahi, Shahriar; Abdollahi, Ami Ardalan; Eskandarinezhad, Mahsa; Negahdari, Ramin; Pakseresht, Zahra (Iranian Endodontic Journal, 2016)
Introduction: This study compared the efficacy of light-activated low-power laser, 2% chlorhexidine (CHX) and 2.5% NaOCl in eliminating Enterococcus faecalis (E. faecalis) from the root canal system. Methods and Materials: The root canals of 60 maxillary central incisors were contaminated with E. faecalis and then the bacteria were incubated for 24 h. All the root canals were instrumented in a crown-down manner with #4 and 3 Gates-Glidden drills, followed by RaCe rotary files (40/0.10, 35/0.08, and 30/0.06). The samples were randomly assigned to three experimental groups and one control group (n=15). In the control group no intervention was made. In the photo-activated disinfection (PAD) group, laser therapy was undertaken with diode laser beams (with an output power of 100 mW/cm2) for 120 sec. For the other two experimental groups, root canals were irrigated either with 5 mL of 2% CHX or 2.5% NaOCl solutions, respectively. The Kruskal-Wallis test was used to compare the CFU values of the bacteria and post-hoc Bonferroni test was used for pairwise comparisons. The level of significance was set at 0.05. Results: The inhibition of bacterial growth in all the experimental groups was significantly superior to the control group (P<0.05). There was no significant difference between the effect of PAD and 2% CHX (P=0.05). The effect of 2.5% NaOCl was significantly better than that of the PAD technique (P<0.001). In addition, 2.5% NaOCl was significantly better than 2% CHX (P=0.007). Conclusion: Photodynamic therapy was effective in reducing the E. faecalis counts in comparison with the control group, but 2.5% NaOCl solution was the most effective protocol. Keywords: Enterococcus faecalis; Laser; Photo-Activated Disinfection; Photodynamic Therapy; Sodium Hypochlorite